2020
DOI: 10.1007/s43440-020-00106-1
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-induced peripheral neuropathy—part 2: focus on the prevention of oxaliplatin-induced neurotoxicity

Abstract: Background Chemotherapy-induced peripheral neuropathy (CIPN) is regarded as one of the most common dose-limiting adverse effects of several chemotherapeutic agents, such as platinum derivatives (oxaliplatin and cisplatin), taxanes, vinca alkaloids and bortezomib. CIPN affects more than 60% of patients receiving anticancer therapy and although it is a nonfatal condition, it significantly worsens patients' quality of life. The number of analgesic drugs used to relieve pain symptoms in CIPN is very limited and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 154 publications
(193 reference statements)
1
82
0
Order By: Relevance
“…[ 32,34 ] In contrast to this, chronic peripheral neuropathy after oxaliplatin treatment is mainly due to a permanent distal sensory loss, the death of sensory neurons, and nerve cell necrosis, which all result from binding of oxaliplatin to mitochondrial DNA. [ 29,35 ] As shown in Figure 3, compound 6 reduced cold allodynia mainly in the acute phase of neuropathy, which suggests its potential action through VGSCs, VGCCs, or other types of ion channels. Compound 7 was not effective in the cold plate test, and although the in vitro part of the present study showed its effect on VGSCs and VGCCs, this activity of compound 7 was not strong enough to provide effective attenuation of cold‐exacerbated pain.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…[ 32,34 ] In contrast to this, chronic peripheral neuropathy after oxaliplatin treatment is mainly due to a permanent distal sensory loss, the death of sensory neurons, and nerve cell necrosis, which all result from binding of oxaliplatin to mitochondrial DNA. [ 29,35 ] As shown in Figure 3, compound 6 reduced cold allodynia mainly in the acute phase of neuropathy, which suggests its potential action through VGSCs, VGCCs, or other types of ion channels. Compound 7 was not effective in the cold plate test, and although the in vitro part of the present study showed its effect on VGSCs and VGCCs, this activity of compound 7 was not strong enough to provide effective attenuation of cold‐exacerbated pain.…”
Section: Resultsmentioning
confidence: 96%
“…Neurotoxicity of oxaliplatin appears in two distinct forms, that is, acute and chronic. [ 29 ] We aimed to test compounds 6 and 7 during both these phases of CIPN to elucidate potential mechanisms underlying in vivo activity of these compounds. Acute neuropathy caused by oxaliplatin results from a transient impairment of ion channels and nerve hyperexcitability due to VGSC activation [ 30–32 ] and VGCC activation.…”
Section: Resultsmentioning
confidence: 99%
“…As other platinum-based compounds (e.g., cisplatin and carboplatin), oxaliplatin impairs the proliferation of tumor cells by forming deoxyribonucleic acid-platinum adducts and this activity results in cancer cell death. In humans, oxaliplatin is used in combination with folinic acid and 5-fluorouracil (FOLFOX therapy) or with folinic acid, 5-fluorouracil and irinotecan (FOLFOXIRI therapy) as the first-line or adjuvant treatment of colorectal cancer [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of note, oxalate that is formed from oxaliplatin is responsible for the observed cold-induced hypersensitivity in patients on oxaliplatin therapy. Oxalate acts as a calcium chelator, which stimulates the removal of extracellular calcium ions, and this leads to the increased sodium conductance, neuronal depolarization and hyperexcitability [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation